2017
DOI: 10.3389/fcell.2017.00040
|View full text |Cite
|
Sign up to set email alerts
|

Control of Neuronal Migration and Aggregation by Reelin Signaling in the Developing Cerebral Cortex

Abstract: The mammalian cerebral neocortex has a well-organized laminar structure, achieved by the highly coordinated control of neuronal migration. During cortical development, excitatory neurons born near the lateral ventricle migrate radially to reach their final positions to form the cortical plate. During this process, dynamic changes are observed in the morphologies and migration modes, including multipolar migration, locomotion, and terminal translocation, of the newborn neurons. Disruption of these migration pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
85
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 76 publications
(110 reference statements)
0
85
0
Order By: Relevance
“…Neurons subsequently generated in the VZ invade and split the preplate, resulting in the formation of two distinct layers: the marginal zone (MZ) and the deep subplate. Newborn neurons then migrate radially from the VZ, pass through the subplate, and stop beneath the MZ to form the CP (Hirota and Nakajima, 2017). Interestingly, our results demonstrated that following single sevoflurane exposure for 2 h, transfected cells were almost all positioned within the UpCP.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons subsequently generated in the VZ invade and split the preplate, resulting in the formation of two distinct layers: the marginal zone (MZ) and the deep subplate. Newborn neurons then migrate radially from the VZ, pass through the subplate, and stop beneath the MZ to form the CP (Hirota and Nakajima, 2017). Interestingly, our results demonstrated that following single sevoflurane exposure for 2 h, transfected cells were almost all positioned within the UpCP.…”
Section: Discussionmentioning
confidence: 99%
“…The first generated cells during corticogenesis form the preplate, which splits and differentiates into the marginal zone (MZ) and the subplate after newly born excitatory neurons start to migrate toward the pial surface (Hirota & Nakajima, ). The neuronal migration is guided by a scaffold called radial fibers of the radial glial cells, which extend to the pial surface (Rakic, , ).…”
Section: Introductionmentioning
confidence: 99%
“…subplate after newly born excitatory neurons start to migrate toward the pial surface (Hirota & Nakajima, 2017). The neuronal migration is guided by a scaffold called radial fibers of the radial glial cells, which extend to the pial surface (Rakic, 1972(Rakic, , 1988.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NCad is upregulated on the cell surface at both these stages in response to an extracellular signal, Reelin. Reelin is known to regulate neuron migration and cortical development by stimulating signaling pathways involving Src kinases, Dab1, PI3' kinase, Crk/CrkL, C3G, and the small GTPase, Rap1 (14)(15)(16)(17)(18)(19)(20)(21). Rap1 then regulates NCad surface expression, presumably through Rab GTPase-dependent vesicular trafficking events (9,11,22).…”
Section: Introductionmentioning
confidence: 99%